Blunders in international business - Ricks, David A. (Oxford : Blackwell Business, 2000)
Introduction. Production. Names. Marketing. Translation. Management. Strategic management. Other areas of International business. Lessons learned.
Keywords: Business; Management; Enterprises; International business enterprises -- Management -- Case studies; Business failures -- Case studies